Harriette Simpson Arnow : Critical Essays on Her Work. - Chung, Haeja K. (Michigan State University Press, 1995)
At her death in 1986, Harriette Simpson Arnow left a modest collection of published work: ten short stories, five novels, two non-fiction books, a short autobiography, and nineteen essays and book reviews. Although the sum is small, her writing has been examined from regionalist, Marxist, feminist, and other critical perspectives. The 1970s saw the first serious attempts to revive interest in Arnow. In 1971, Tillie Olsen identified her as a writer whose ""books of great worth suffer the death of being unknown, or at best, a peculiar eclipsing."" Joyse Carol Oates wrote in.